The Influence of Merdeka Belajar – Kampus Merdeka to Improve the Quality of Graduates in Higher Education: A Reflective Analysis - Paisal Manurung; Hamidah Sidabalok; Muhammad Sepristiwanto; Cindy Purnama Sari Az Zahra; Nur Rahmana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Higher education is vital in producing qualified graduates ready to face work challenges. This research used a case study approach at Asahan University. This study aimed to analyze the effect of the Merdeka Belajar-Kampus Merdeka program at Asahan University. Method: The approach was used as an experimental research approach. The respondents constituted students and lecturers at the Faculty of Teacher Training and Education at Asahan University, which accounts for 26 participants. In sampling from the population, researchers used purposive sampling with sample characters, namely students and lecturers of the Faculty of Teacher Training and Education, students and lecturers involved in the MBKM program batch 1 to batch 6. Data collection was carried out using 20 questionnaires, which were analyzed using a Likert Scale. The data was collected using the Google form integrated with Internet-Based Data Analysis (IBDA) and analyzed using the Microsoft Office Excel formula. Results: Therefore, based on the questionnaire distributed using Google Forms, it was found that the program MBKM that Asahan University has carried out affects the competence of graduates involved in the program, with a significance of 64.4% with significant criteria. Novelty: Based on the analysis and discussion results, the Learning Management System integrated the MBKM program to require a clear, structured concept and scientific transparency in all aspects to increase the number of graduates who contribute to the development of Indonesia Maju 2045.